Implementation of Colorful Ball Games to Enhance Gross Motor Skills of Children Aged 4–5 Years At Paud An-Naba: Implementasi Permainan Bola Warna Warni Dalam Menumbuhkan Kemampuan Motorik Kasar Anak Usia 4-5 Tahun Di Paud An-Naba - Ahyuroh, Ahyuroh; Risna, Inten; Mutaqin, Moh Fikri Tanzil; Umalihayati, Umalihayati; Mutoharoh, Mutoharoh (Universitas Muhammadiyah Sidoarjo, 2025)
This research was motivated by the fact that some children aged 4–5 years at PAUD An-Naba still experienced difficulties in gross motor development, such as jumping, throwing a ball accurately, and maintaining balance. The purpose of this study was to describe the implementation of colorful ball games in learning activities and to analyze the gross motor development of children after the activity. This study employed a descriptive qualitative approach with subjects consisting of children aged 4–5 years at PAUD An-Naba. Data were collected through observation, interviews, and documentation, and analyzed using Miles & Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the implementation of colorful ball games was carried out through planning, implementation, and evaluation stages. Children were enthusiastic and motivated to participate because the colorful balls attracted their attention. The gross motor development of children improved in terms of strength, balance, and coordination after the activities. This study concludes that colorful ball games are effective as a fun, low-cost, and easily applicable learning strategy to stimulate gross motor development in early childhood.